2010
DOI: 10.1016/j.ydbio.2010.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Different requirements for conserved post-transcriptional regulators in planarian regeneration and stem cell maintenance

Abstract: Planarian regeneration depends on the presence and precise regulation of pluripotent adult somatic stem cells named neoblasts, which differentiate to replace cells of any missing tissue. A characteristic feature of neoblasts is the presence of large perinuclear nonmembranous organelles named "chromatoid bodies", which are comparable to ribonucleoprotein structures found in germ cells of organisms across different phyla. In order to better understand regulation of gene expression in neoblasts, and potentially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 112 publications
9
113
1
Order By: Relevance
“…Cells expressing #008 (piwiA) completely disappeared in the X-ray-irradiated animals ( Fig. 3D), indicating that this gene was specifically expressed in the neoblasts, as previously described (Yoshida-Kashikawa et al, 2007;Rouhana et al, 2010;Shibata et al, 2010). Genes such as #012 (P2X-A) and #032 (unknown) showed the same expression patterns as #008 (piwiA) in intact and X-ray-irradiated animals (data not shown).…”
Section: Expression Analyses Of Hicep Genes By In Situ Hybridizationsupporting
confidence: 82%
See 1 more Smart Citation
“…Cells expressing #008 (piwiA) completely disappeared in the X-ray-irradiated animals ( Fig. 3D), indicating that this gene was specifically expressed in the neoblasts, as previously described (Yoshida-Kashikawa et al, 2007;Rouhana et al, 2010;Shibata et al, 2010). Genes such as #012 (P2X-A) and #032 (unknown) showed the same expression patterns as #008 (piwiA) in intact and X-ray-irradiated animals (data not shown).…”
Section: Expression Analyses Of Hicep Genes By In Situ Hybridizationsupporting
confidence: 82%
“…#008 (piwiA), showed a typical pattern of neoblast-specific expression, in which the distribution of positive cells was observed in the mesenchymal space from behind the eyes to the tail ( Fig. 3C; Yoshida-Kashikawa et al, 2007;Rouhana et al, 2010;. Cells expressing #008 (piwiA) completely disappeared in the X-ray-irradiated animals ( Fig.…”
Section: Expression Analyses Of Hicep Genes By In Situ Hybridizationmentioning
confidence: 92%
“…CBs are electron dense perinuclear granules composed of RNA and proteins that decrease in number and size during cell differentiation, and, for this reason, are thought to be required for neoblast self-renewal and proliferation . In support of this hypothesis, a set of RNA-binding factors has been found to be necessary to maintain neoblast pluripotency (YoshidaKashikawa et al, 2007;Rouhana et al, 2010), and silencing of Smed-SmB, a homolog of a member of the LSm protein family, results in loss of CBs organization and severe neoblasts proliferation failure (Fernandéz-Taboada et al, 2010). Moreover, Solana and colleagues (2009) demonstrated that a tudor homolog, Spoltud-1, is a component of CBs and is required for neoblast maintenance.…”
Section: Neoblastsmentioning
confidence: 99%
“…Recent studies in planarians identified several genes that encode RNA binding proteins such as TIA-1, LSm, eIF-4A, eIF-4G, TRDR-1, SMN, CBC-1, TUD-1, PIWI, DICER-1, FMRP-1 and Ago-2. These genes are expressed in neoblasts and some of them were shown to be essential for neoblast function and regeneration (Rouhana et al, 2010). In C. elegans, Drosophila and mammals, most of these proteins are associated with various RNP granules such as P-bodies, stress granules and chromatoid bodies (Kotaja et al, 2007).…”
Section: Planarian Mirnasmentioning
confidence: 99%